Methods of Management Activities in the Ensuring of Constitutional Socio-Economic Rights of Citizens of the Russian Federation - Ol'ga M. Gvozdeva (Сибирское юридическое обозрение, 2017)
In this paper based on theory and practice an analysis is given of the application of the methods of management activities for the realization of the constitutional socio-economic rights of citizens of the Russian Federation.